STRATEGI RELAKSASI UNTUK MEMBANTU SISWA YANG MENGALAMI STRES BELAJAR DI KELAS 9D SMP NEGERI 1 MEJAYAN KABUPATEN MADIUN - Bambang Agus Pramunto (Counsellia: Jurnal Bimbingan dan Konseling, 2015)
Along with the advancement of science and technology, the problems facedby individuals increasingly complex. A problem that can not be avoided bystudents in general and students in grade 9 in particular is a matter of learning.Slowly but surely grade 9 students have to face the "Monster" in completing hiseducation at the junior high school is very popular so-called UN. Phenomena inthe field seen many students are scrambling to prepare. They forge themselvesparticipate tutoring outside of school and at school, and a number are still callinga tutor Evenmore ironic ladies and teachers provide enormous task. Classroom ActionResearch (CAR) is implemented in order to help students overcome problemsrelated to distress (stress) on the learner as tired of learning. Help is alleviation,with the expectation that students face problems (stress learning) can understandyourself, set yourself and can eventually adapt to the problems that it faces.Relaxation strategy is one of the techniques in guidance and counselingservices aimed at helping students to release tension and fatigue in this case is thestate of stress related to learning activities.Research methods by using several instruments including a questionnaire(stress questionnaire study), namely Stress Questionnaire Learning is used todetermine and measure the students who have studied the stress levelsencountered during the pre-test and post-test, manual observation and interviewguidelines.Technical analysis of the data, using qualitative analysis, but also supported byquantitative analysis. Quantitative analysis is used when processing data StressStudy questionnaire in order to determine the level of stress category learningexperienced by learners.In this study there are two cycles. Conclusions on pre-research activitiesoutlined in the initial reflection.